(untitled) - Sirota, Audrey J. (San Francisco, CA, 2006)
The Heart of Teaching offers practical guidance in designing lessons and classroom activities that are powerfully effective for all types of students, including those placed at risk of educational failure due to linguistic, socioeconomic, racial, and geographic factors. The approach is easily geared to standards and can be used to strengthen and enrich scripted lessons or mandated curricular units. With a strong emphasis on literacy, the book shows teachers how to assess a lesson plan and then how to design activities and exercises that can meaningfully engage all students, even those who have difficulty in school. The book also shows teachers how to use learning centers for differentiating lessons and for breaking the classroom into small, participatory settings.
Keywords: High school teaching,Effective teaching,Motivation in education,Giáo dục trung học,Hiệu quả giảng dạy,Động lực trong giáo dục